DEVELOPMENT OF TEACHING MATERIALS IN THE FORM OF DIGITAL MAGAZINES FLIPBOOK APPLICATION HELPED ON MATERIALS DESCRIPTION TEXT OF CLASS VII STATE JUNIOR HIGH SCHOOL 35 MEDAN - Mariance Sinambela; M. Joharis Lubis (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
The problem in this study is that the descriptive text material in the teaching materials used by the teacher does not explain the material in depth, causing difficulties for students in learning descriptive text which does not achieve achievement indicators that are in accordance with basic competencies. This study aims to develop descriptive text material in the form of a digital magazine with the help of a flipbook application to make it easier for students to learn descriptive text and can be used in the learning process to make it more effective and efficient. The subjects in this study were class VII - 8 students of SMP Negeri 35 Medan, expert validators of instructional media design and material expert validators. The object of this research is Teaching Materials of Description Texts in the Form of Digital Magazines Assisted by Flipbook Applications in class VII students. This type of research is carried out by R&D (Research and Development) by applying the Borg and Gall development model. The developed product is validated by material experts and media experts to test the feasibility of the product being developed. The score obtained for the material validation results was 80% in the "good" category and the score obtained for the design validation was 83% in the "very good" category. Based on the results of this validation, it can be concluded that the product developed is declared feasible for use in the learning process.  Keywords: Development, Teaching Materials, Description Text.